A Survey on Different Uses of Sugarcane in Different States of India (International Journal of Innovative Research in Engineering & Management, 2021)
Sugarcane is a perennial grass that is planted in various regions  of the country. Each state has a unique Sugarcane need, and each  state requires a comparatively large quantity of Sugarcane for that  particular industrial application. However, it is a question of study  to determine which state in India requires more sugarcane for a  certain industrial requirement. It will be easier to enhance crop  output according to the industrial demand in that state by  evaluating the relative demand of sugarcane for industrial  production of certain items. Thus, the current study sheds light on  the demand for sugarcane for various purposes in the states of  Uttar Pradesh, Gujarat, Maharashtra, and Tamil Nadu, and it pave  the way for future research into the relationship between different  varieties of cereals and pulses and average consumption of that  variety in a given state.
Keywords: Alcohol; Bio-Plastic; Cane; Fertilizer; Skin Care